Official and Unofficial US NAVY AIR PATCHES : 1920s to Today - Nelson, Derek, 1950-; Parsons, Dave, 1954- (Motorbooks International, 1990)
Motorbooks International. This fine book presents a gallery of more than 500 patches in full-color, and many more in black and white. Within are the well-known insignia for squadrons such as the "Grim Reapers", the "Red Rippers", and the "Pukin' Dogs", as well as hundreds of seldom-seen and unofficial squadron patches